Crystal structure and magnetocaloric effect of non-rare-earth KBa8Fe12(Bi6−xFex)O38. Issue 3 (8th December 2022) - Wu, Xuan; Deng, Yanyun; Wu, Shuting; Chen, Xin; Hu, Xiaolin; Zhuang, Naifeng
Abstract : Non-rare-earth cubic crystal of KBa8 Fe12 (Bi6− x Fe x )O38 is constructed to have strong MCE at ultra-low temperature. Abstract : The 6p orbit coupling of bismuth ions and the magnetism of iron ions endow bismuth–iron compounds with magnetic, optical and electrical properties. In this paper, non-rare-earth bismuth–iron crystals, KBa8 Fe12 (Bi6− x Fe x )O38 ( x = 0.2, 1.1, 2.0, 2.9, and 3.8), with a large magnetocaloric effect were prepared by a hydrothermal method. The structure–function relationship is discussed. With the increase of the Fe content, the lattice parameters and unit cell volume decrease, while the magnetization intensity shows an increase on the whole and a fluctuation at the same time. The increase of the Fe content can improve the magnetocaloric effect. Importantly, the maximum magnetic entropy change (Δ S M ) of KBa8 Fe12 (Bi4.9 Fe1.1 )O38 is as high as 1.54 J kg −1 K −1 at the low temperature of 2 K.